Pengembangan Website Pariwisata Religi Berbasis Informasi dan Tiket Online (Studi Kasus: Museum Al-Qur’an Akbar Palembang) - Nada Salsabilah; Aulia Syalsabila; Yuliana Almunawaroh; Rafa Lutfyah; Anugerah Widi (Universitas Multi Data Palembang, 2026)
The development of digital technology has driven service transformation across various sectors, including tourism, particularly religious tourism, which requires easy access to information and efficient visitor services. Museum Al-Qur’an Akbar Palembang, as a religious and educational tourism destination, faces challenges in managing visitor information and ticket reservation services that are still largely conventional and not yet fully oriented toward user experience. This study aims to design the user interface and user experience (UI/UX) of an information and online ticketing website by applying the Design Thinking method. The method is implemented through five stages empathize, define, ideate, prototype, and test to systematically identify the needs and problems of both visitors and museum managers and translate them into digital design solutions. The results show that the application of Design Thinking contributes to the development of a website prototype that supports service efficiency, improves information clarity, enhances navigation comfort, and aligns user needs with museum management requirements. This research provides a contribution to the development of user-centered digital services for religious tourism and may serve as a reference for the design of similar systems in other religious and cultural tourism destinations.